B and N co-doped carbon nanotube loaded copper-iron bimetallic oxide catalyst as well as preparation and application thereof

By preparing B and N co-doped carbon nanotubes by electrochemical reduction of nitrates, the B and N co-doped carbon nanotubes were prepared by calcining method, and the copper-iron bimetal oxide cluster structure was formed by high-temperature pyrolysis, the complex 8-electron transfer process and the side reactions and low selectivity problems caused by multiple intermediates in the prior art were solved, and efficient nitrate reduction and ammonia preparation were achieved.

CN120210859AActive Publication Date: 2025-06-27SHANTOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510695147.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-06-27
Estimated Expiration
2045-05-28

AI Technical Summary

Technical Problem

The prior art has complex 8-electron transfer process and a variety of intermediates in the preparation of ammonia by electrochemical reduction nitrates, resulting in side reactions and low selectivity, making it difficult to design and build an efficient catalytic system.

Method used

The B and N co-doped carbon nanotubes were prepared by calcining method, and the copper-iron metal ions were loaded on the surface of the carbon nanotubes by immersion and adsorption method, and then high-temperature pyrolysis was performed to form a copper-iron bimetallic oxide cluster structure.

Benefits of technology

It achieves high ammonia production efficiency and high Faraday efficiency, providing a simple and universal electrocatalytic nitrate reduction method, significantly improving the nitrate reduction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120210859A_ABST
    Figure CN120210859A_ABST
Patent Text Reader

Abstract

The invention relates to a B and N co-doped carbon nanotube loaded copper-iron bimetallic oxide catalyst and preparation and application thereof.The B and N co-doped carbon nanotube is prepared through a calcination method, metal ions are adsorbed to the surface of a carbon material through a soaking adsorption method, then the carbon material is placed in a tubular furnace and subjected to high-temperature pyrolysis in the argon atmosphere, and the copper-iron bimetallic oxide catalyst loaded with the B and N co-doped carbon nanotube is obtained. The size and density of metal active sites on the surface of the carbon material can be regulated and controlled by regulating and controlling the concentration, proportion and temperature of metal ions, and a bimetallic oxide cluster structure is constructed. The obtained carbon nanotube material retains the complete structure of the carbon material, a large number of copper-iron bimetal oxide clusters are constructed and loaded on the surface, the material capable of effectively promoting electro-catalysis nitrate reduction to produce ammonia is prepared, the nitrate reduction performance can be effectively improved, the yield is obviously improved, and the method is suitable for industrial production. And the ammonia production rate of 95.2 mgh <-1 > mgcat <-1 > and the Faraday efficiency of 91.3% can be achieved under the potential of-0.8 VRHE.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic reduction of nitrate to ammonia, and particularly relates to a copper-iron bimetallic oxide catalyst supported on B, N co-doped carbon nanotubes and its preparation and application. Background Art

[0002] Traditional ammonia synthesis processes need to be carried out under high temperature and high pressure and emit a large amount of carbon dioxide. Electrochemical reduction of nitrate, as a mild green ammonia synthesis technology, has attracted much attention. Its main advantages are that the N=O bond energy in nitrate (204 kJ / mol) is much lower than the N≡N bond energy in N2 molecules (941 kJ / mol), and it has extremely high solubility in water, reducing the reaction thermodynamic energy barrier. In addition, nitrate is the main component of current water body nitrogen pollutants. Converting it into available energy is an excellent strategy for turning waste into treasure, and it can also be used as a good hydrogen storage strategy to provide high-quality energy for production and life. However, this reaction involves a complex 8-electron transfer process and multiple intermediates, which easily leads to side reactions and low selectivity. Therefore, designing and constructing an efficient catalytic system to improve the selectivity and Faraday efficiency of nitrate reduction is crucial. Summary of the Invention

[0003] The purpose of the present invention is to provide a copper-iron bimetallic oxide catalyst supported on B, N co-doped carbon nanotubes and its preparation and application to solve the problems existing in the prior art.

[0004] By simple technical means, the present invention uniformly mixes perylene tetracarboxylic dianhydride, boric acid, and urea and calcines them to construct carbon nanotubes with B and N co-doping, adjusts their doping amounts, and loads metal atoms on their surfaces through a coordination adsorption strategy, and obtains a catalyst with high nitrate reduction ammonia production efficiency and high Faraday efficiency through pyrolysis.

[0005] A preparation method of a copper-iron bimetallic oxide catalyst supported on B, N co-doped carbon nanotubes includes the following steps: (1) Uniformly mix an aromatic compound, boric acid, and urea in an organic solvent, and then remove the organic solvent; (2) Then place it in a tube furnace and calcine it at 400 - 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes; (3) After washing, filtering, and drying the B, N co-doped carbon nanotubes obtained in step (2), soak them in a solution containing copper and iron metal ions, and then wash and dry them; (4) Then place it in a tube furnace and pyrolyze it at 300 - 480 °C for 1 - 4 hours in an inert gas atmosphere to obtain a copper-iron bimetallic oxide catalyst supported on B, N co-doped carbon nanotubes.

[0006] In step (2), if the calcination temperature is higher than 800 °C, the carbon material will decompose excessively, and carbon nanotubes with a smooth surface cannot be obtained, and it may even decompose completely; if it is lower than 400 °C, the precursor red powder cannot be completely carbonized, and carbon nanotubes cannot be obtained, but flakes will be obtained.

[0007] Furthermore, the aromatic compound described in step (1) is one or more of perylene tetracarboxylic dianhydride, anthracene, quinone, and phenanthrene.

[0008] Furthermore, when the aromatic compound is perylene tetracarboxylic dianhydride, the mass ratio of perylene tetracarboxylic dianhydride, boric acid, and urea added is 10: 0.1 - 10: 80 - 89.8. If too much boric acid is added, the resulting material will not be carbon nanotubes, but a material such as boron carbide.

[0009] Furthermore, the organic solvent in step (1) is ethanol. Ethanol is a solvent with good solubility and easy to remove. It was found during the exploration that using other solvents could not achieve the effect of ethanol as a solvent.

[0010] Furthermore, the solution containing copper and iron metal ions in step (3) is a mixed solution of copper chloride and iron chloride.

[0011] Furthermore, the mass ratio of copper chloride to iron chloride is 1 - 10: 1 - 10. The best effect is achieved when the mass ratio of copper chloride to iron chloride is 5: 5.

[0012] Furthermore, the addition amount of B, N co-doped carbon nanotubes in step (3) is 100 - 300 mg, and the addition amount of the mixed solution of copper chloride and iron chloride is 1 - 4 mmol.

[0013] After doping B and N on the surface of carbon nanotubes in the present invention, metal ions are adsorbed on the surface of the carbon material, and the formation of copper-iron bimetallic oxide clusters is realized by high-temperature pyrolysis. Most of the existing processes use the pyrolysis of pre-prepared MOF materials to prepare bimetallic catalysts, while the present invention uses high-temperature pyrolysis to construct a new structure. In addition, in the present invention, B is mixed with perylene tetracarboxylic dianhydride and carbonized together. During the carbonization process, B is located in the carbon nanotubes and is not doped by grafting. The B-doped carbon nanotubes obtained in the present invention are more uniform, and it is easier to incorporate B into the carbon nanotubes. The experimental operation and principle are simpler.

[0014] The B, N co-doped carbon nanotube-supported copper-iron bimetallic oxide catalyst prepared by the above preparation method includes a carbon nanotube material with B, N co-doping and metal oxide nanoparticles supported on the surface of the carbon nanotubes. In the B, N co-doped carbon nanotube-supported copper-iron bimetallic oxide catalyst of the present invention, the B, N co-doping synergizes with each other. The role of the N atom is to coordinate and anchor metal atoms and simultaneously regulate their electronic structure to promote the nitrate reduction process; the role of the B atom is to form an electron-deficient center on the carbon tube surface, thereby adsorbing nitrate ions, increasing the nitrate concentration near the electrode, and thus promoting nitrate reduction.

[0015] While enhancing the nitrate adsorption capacity through B doping, the present invention anchors metal atoms through N to fix them on the surface of carbon nanotubes, forming an electrocatalytic nitrate reduction material with a high ammonia production rate and high Faraday efficiency for nitrate reduction, providing a simple and universal method for electrocatalytic nitrate reduction and offering a useful reference for the research and development of high-performance nitrate reduction materials.

[0016] The N atoms doped in the carbon nanotubes have good adsorption properties for metal ions. After doping N on the surface of the carbon nanotubes and then adsorbing metal ions, the adsorption of metal ions can be regulated, thereby realizing the dispersion regulation of metal ions on the surface of the carbon-based material, enabling the precise control of the size of the metal oxide nanoparticles formed during the high-temperature process and thus increasing the number of active sites. B is used to control the adsorption of nitrate, thereby accelerating the transfer process on the electrode surface or the catalyst surface. The doping of B atoms generates an electron-deficient center on the surface of the carbon nanotubes, which is beneficial to the adsorption of nitrate ions and further accelerates the nitrate reduction rate. Carbon nanotubes are used for electron conduction.

[0017] Copper and iron metal ions are the active centers for nitrate reduction. By regulating the metal ion loading amount, ratio, and pyrolysis temperature, the amount of metal oxides supported on the surface of the carbon nanotube material can be regulated, forming oxide clusters with different sizes and densities on the surface of the carbon material, thereby constructing active centers for nitrate reduction.

[0018] The application of the above electrocatalytic material is used for nitrate reduction to produce ammonia, nitrate degradation, etc. Compared with the prior art, in the present invention, B, N co-doped carbon nanotubes are prepared by a calcination method, and metal ions are adsorbed on the surface of the carbon material by an immersion adsorption method. Then, the material is placed in a tube furnace and pyrolyzed at a high temperature in an argon atmosphere. The size and density of the metal active sites on the surface of the carbon material can be regulated by controlling the metal ion concentration, ratio, and temperature, and a bimetallic oxide cluster structure is constructed. The carbon nanotube material obtained in the present invention not only retains the complete structure of the carbon material itself but also has a large number of copper-iron bimetallic oxide clusters loaded on the surface structure. The role of the N atom is to coordinate and anchor metal atoms and simultaneously regulate their electronic structures to promote the nitrate reduction process; the role of the B atom is to form an electron-deficient center on the surface of the carbon tube, thereby adsorbing nitrate ions, increasing the nitrate concentration near the electrode, and thus promoting nitrate reduction. The catalyst obtained in the present invention can effectively promote the electrocatalytic reduction of nitrate to ammonia, effectively improve the nitrate reduction performance, and significantly increase the yield. At a potential of -0.8V RHE the ammonia production rate can reach 95.2 mgh -1 mg cat -1 and a Faraday efficiency of 91.3%. Description of the Drawings

[0019] Figure 1 is the surface morphology diagram of the B, N co-doped carbon nanotubes of Example 1; Figure 2 is the surface morphology diagram of the B, N co-doped carbon nanotubes after loading copper-iron bimetallic oxides in Example 1; Figure 3 is the elemental analysis diagram of the B, N co-doped carbon nanotubes after loading copper-iron bimetallic oxides in Example 1; Figure 4 is the XRD diagram of the B, N co-doped carbon nanotubes before and after loading metal oxides in Example 1; Figure 5 is the high-resolution diagram of the B, N co-doped carbon nanotubes after loading copper-iron bimetallic oxides in Example 1; Figure 6 is the nitrate reduction performance diagram of the B, N co-doped carbon nanotubes loaded with copper-iron bimetallic oxides in Example 1 at different potentials; Figure 7 is the performance comparison diagram of the B, N co-doped carbon nanotubes loaded with copper-iron bimetallic oxides in Example 1 and the N-doped carbon nanotubes loaded with copper-iron bimetallic oxides in Comparative Example 2 at different nitrate concentrations; Figure 8 is the morphology of the B, N co-doped carbon nanotubes loaded with copper-iron bimetallic oxides prepared in Example 1 after pyrolysis at 500 °C for 4 hours; Figure 9 It is a performance comparison chart of the catalysts of Example 5 and Example 1; Figure 10 It is a performance comparison chart of the catalysts of Example 6, 7 and Example 1; Figure 11 It is a performance comparison chart of the catalysts of Example 8 and Example 1; Figure 12 It is a morphology chart of the catalyst of Example 9. Detailed implementation manners

[0020] To make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings.

[0021] Example 1 Weigh 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea, mix them evenly with 40 mL of ethanol as the solvent, then remove the solvent by rotary evaporation and then vacuum dry to obtain a red mixture; then place it in a tube furnace and calcine at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes, denoted as N,B-CNTs; transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat to 80 °C and stir for 30 minutes; then filter and dry, and then weigh 300 mg from them and transfer it to a beaker, add 40 mL of water, and add a total of 3 mmol of copper chloride and iron chloride in a ratio of 5:5, stir at room temperature for 10 hours, filter, wash, and dry, and then place it in a tube furnace and pyrolyze at 400 °C in an inert gas atmosphere for 3 hours to obtain a B, N co-doped carbon nanotube supported copper-iron bimetallic oxide catalyst, denoted as CuFeOx / BNCNTs.

[0022] Example 2 Weigh 810 mg of perylene tetracarboxylic dianhydride, 81 mg of boric acid, and 6.62 g of urea, mix them evenly with 40 mL of ethanol as the solvent, then remove the solvent by rotary evaporation and then vacuum dry to obtain a red mixture; then place it in a tube furnace and calcine at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes; transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat to 80 °C and stir for 30 minutes; then filter and dry, and then weigh 300 mg from them and transfer it to a beaker, add 40 mL of water, and add a total of 3 mmol of copper chloride and iron chloride in a ratio of 5:5, stir at room temperature for 10 hours, filter, wash, and dry, and then place it in a tube furnace and pyrolyze at 400 °C in an inert gas atmosphere for 3 hours to obtain a B, N co-doped carbon nanotube supported copper-iron bimetallic oxide catalyst.

[0023] Example 3 810 mg of perylene tetracarboxylic dianhydride, 814 mg of boric acid, and 6.62 g of urea were weighed and uniformly mixed with 40 mL of ethanol as a solvent. Then, the solvent was removed by rotary evaporation and then vacuum dried to obtain a red mixture. Then, it was placed in a tube furnace and calcined at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. The carbon nanotubes were transferred to a beaker, an appropriate amount of water was added, and the mixture was heated to 80 °C and stirred for 30 minutes. Then, it was filtered, dried, and 300 mg was weighed from it and transferred to a beaker, 40 mL of water was added, and a total of 3 mmol of copper chloride and iron chloride were added in a ratio of 5:5. It was stirred at room temperature for 10 hours, filtered, washed, and dried. Then, it was placed in a tube furnace and pyrolyzed at 400 °C in an inert gas atmosphere for 3 hours to obtain a B, N co-doped carbon nanotube supported copper-iron bimetallic oxide catalyst.

[0024] Example 4 The difference from Example 1 is that the red mixture was placed in a tube furnace and calcined at 400 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes; the others were the same as in Example 1.

[0025] Example 5 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea were weighed and uniformly mixed with 40 mL of ethanol as a solvent. Then, the solvent was removed by rotary evaporation and then vacuum dried to obtain a red mixture. Then, it was placed in a tube furnace and calcined at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. The carbon nanotubes were transferred to a beaker, an appropriate amount of water was added, and the mixture was heated to 80 °C and stirred for 30 minutes. Then, it was filtered, dried, and 300 mg was weighed from it and transferred to a beaker, 40 mL of water was added, and 3 mmol of copper chloride was added. It was stirred at room temperature for 10 hours, filtered, washed, and dried. Then, it was placed in a tube furnace and pyrolyzed at 400 °C in an inert gas atmosphere for 3 hours to obtain a B, N co-doped carbon nanotube supported copper metal oxide catalyst, denoted as CuOx / BNCNTs.

[0026] Example 6 Weigh 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea, and uniformly mix them with 40 mL of ethanol as the solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. Transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat it to 80 °C, and stir for 30 minutes. Then, filter and dry it. Then, weigh 300 mg from it and transfer it to a beaker, add 40 mL of water, and add a total of 3 mmol of copper chloride and iron chloride in a ratio of 3:7. Stir at room temperature for 10 hours, filter, wash, and dry it. Then, place it in a tube furnace and pyrolyze it at 400 °C in an inert gas atmosphere for 3 hours to obtain a B, N co-doped carbon nanotube-supported copper-iron bimetallic oxide catalyst, denoted as Cu3Fe7Ox / BNCNTs.

[0027] Example 7 Weigh 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea, and uniformly mix them with 40 mL of ethanol as the solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. Transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat it to 80 °C, and stir for 30 minutes. Then, filter and dry it. Then, weigh 300 mg from it and transfer it to a beaker, add 40 mL of water, and add a total of 3 mmol of copper chloride and iron chloride in a ratio of 7:3. Stir at room temperature for 10 hours, filter, wash, and dry it. Then, place it in a tube furnace and pyrolyze it at 400 °C in an inert gas atmosphere for 3 hours to obtain a B, N co-doped carbon nanotube-supported copper-iron bimetallic oxide catalyst, denoted as Cu7Fe3Ox / BNCNTs.

[0028] Example 8 Weigh 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea, and uniformly mix them with 40 mL of ethanol as the solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. Transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat it to 80 °C, and stir for 30 minutes. Then, filter and dry it. Then, weigh 300 mg from it and transfer it to a beaker, add 40 mL of water, and add 3 mmol of iron chloride. Stir at room temperature for 10 hours, filter, wash, and dry it. Then, place it in a tube furnace and pyrolyze it at 400 °C in an inert gas atmosphere for 3 hours to obtain a B, N co-doped carbon nanotube-supported iron metal oxide catalyst, denoted as FeOx / BNCNTs.

[0029] Example 9 Weigh 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea, and uniformly mix them with 40 mL of ethanol as a solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. Transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat it to 80 °C, and stir for 30 minutes. Then, filter and dry it. Then, weigh 300 mg from it, transfer it to a beaker, add 40 mL of water, and add a total of 1 mmol of copper chloride and iron chloride in a ratio of 5:5. Stir at room temperature for 10 hours, filter, wash, and dry it. Then, place it in a tube furnace and pyrolyze it at 400 °C for 3 hours in an inert gas atmosphere.

[0030] Example 10 Weigh 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea, and uniformly mix them with 40 mL of ethanol as a solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. Transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat it to 80 °C, and stir for 30 minutes. Then, filter and dry it. Then, weigh 300 mg from it, transfer it to a beaker, add 40 mL of water, and add a total of 2 mmol of copper chloride and iron chloride in a ratio of 5:5. Stir at room temperature for 10 hours, filter, wash, and dry it. Then, place it in a tube furnace and pyrolyze it at 400 °C for 3 hours in an inert gas atmosphere.

[0031] Example 11 Weigh 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea, and uniformly mix them with 40 mL of ethanol as a solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. Transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat it to 80 °C, and stir for 30 minutes. Then, filter and dry it. Then, weigh 300 mg from it, transfer it to a beaker, add 40 mL of water, and add a total of 4 mmol of copper chloride and iron chloride in a ratio of 5:5. Stir at room temperature for 10 hours, filter, wash, and dry it. Then, place it in a tube furnace and pyrolyze it at 400 °C for 3 hours in an inert gas atmosphere.

[0032] Example 12 Weigh 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea, and uniformly mix them with 40 mL of ethanol as the solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. Transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat it to 80 °C, and stir for 30 minutes. Then, filter and dry it. Then, weigh 300 mg from it, transfer it to a beaker, add 40 mL of water, and add a total of 3 mmol of copper chloride and iron chloride in a ratio of 5:5. Stir at room temperature for 10 hours, filter, wash, and dry it. Then, place it in a tube furnace and pyrolyze it at 300 °C in an inert gas atmosphere for 3 hours.

[0033] Example 13 Weigh 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea, and uniformly mix them with 40 mL of ethanol as the solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain B, N co-doped carbon nanotubes. Transfer the carbon nanotubes to a beaker, add an appropriate amount of water, heat it to 80 °C, and stir for 30 minutes. Then, filter and dry it. Then, weigh 300 mg from it, transfer it to a beaker, add 40 mL of water, and add a total of 3 mmol of copper chloride and iron chloride in a ratio of 5:5. Stir at room temperature for 10 hours, filter, wash, and dry it. Then, place it in a tube furnace and pyrolyze it at 500 °C in an inert gas atmosphere for 3 hours.

[0034] Comparative Example 1 Prepare B-doped carbon nanotubes: Weigh 810 mg of perylene tetracarboxylic dianhydride and 570 mg of boric acid, uniformly mix them with 40 mL of ethanol as the solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain B-doped carbon nanotubes. Then, use the method of Example 1 to load copper chloride and iron chloride. It is found that in the absence of N doping, it is difficult for copper and iron metals to be anchored on the carbon nanotubes, and they can only be adsorbed physically. Therefore, their loading amount is very small, and the corresponding performance will also be very low, so that almost no nitrate is reduced to ammonia.

[0035] Comparative Example 2 Prepare N-doped carbon nanotubes: Weigh 810 mg of perylene tetracarboxylic dianhydride and 6.62 g of urea, uniformly mix them with 40 mL of ethanol as the solvent. Then, remove the solvent by rotary evaporation and subsequently dry it under vacuum to obtain a red mixture. Then, place it in a tube furnace and calcine it at 800 °C in an argon atmosphere to obtain N-doped carbon nanotubes. Then, use the method of Example 1 to load copper chloride and iron chloride, and the corresponding performance comparison is as Figure 7 shown.

[0036] Comparative Example 3 The carbon nanotubes were mixed uniformly with boron-containing organic compounds (such as boric acid) and nitrogen-containing organic compounds (such as urea), and then calcined in a tubular furnace at 800 °C under an argon atmosphere to obtain B, N co-doped carbon nanotubes; Then, the method of Example 1 was used to load copper chloride and iron chloride. It was found that for the carbon nanotube material obtained by realizing the doping of B and N in a grafting manner, the anchoring effect on metals was not as good as that of direct doping, and the corresponding agglomeration phenomenon was more serious, so the performance would decline.

[0037] Comparative Example 4 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea were weighed and uniformly mixed with 40 mL of ethanol as a solvent. Then, the solvent was removed by rotary evaporation and then vacuum dried to obtain a red mixture; then, it was placed in a tubular furnace and calcined at 850 °C or 900 °C under an argon atmosphere. The carbon material would decompose excessively and smooth-surfaced carbon nanotubes could not be obtained, and even complete decomposition occurred.

[0038] Comparative Example 5 810 mg of perylene tetracarboxylic dianhydride, 570 mg of boric acid, and 6.62 g of urea were weighed and uniformly mixed with 40 mL of ethanol as a solvent. Then, the solvent was removed by rotary evaporation and then vacuum dried to obtain a red mixture; then, it was placed in a tubular furnace and calcined at 350 °C under an argon atmosphere. The precursor red powder could not be completely carbonized, and carbon nanotubes could not be obtained, but flakes were obtained.

[0039] Performance detection From Figure 1 It can be seen that the B, N co-doped carbon nanotubes of the present invention are uniform in size and widely distributed.

[0040] From Figure 2 It can be seen that the copper-iron bimetallic oxide is uniformly and densely distributed on the surface of the carbon nanotubes. The existence form of B in the carbon tubes directly formed by calcination is distributed in the carbon tubes, and no other situations such as grafting are observed through SEM and other characterizations.

[0041] From Figure 3 It can be seen that the metal is successfully adsorbed on the surface of the carbon nanotubes.

[0042] From Figure 4 It can be seen that after the metal oxide is loaded, no obvious absorption peaks appear in its XRD, which confirms the uniform distribution of the metal oxide on the carbon nanotubes and no agglomeration phenomenon occurs (the CuFeOx / NBCNTs and NBCNTs shown are both materials of Example 1).

[0043] The morphology of the specific bimetallic oxide clusters of the material is as Figure 5As shown, by Figure 5 It can be seen that there are multiple crystal phases within the range shown in the figure, confirming the formation of bimetallic oxide clusters.

[0044] The performance advantages of the material are mainly reflected in two aspects: high ammonia production performance and excellent Faraday efficiency. Different copper-iron ratios have been tried, and they all have certain nitrate reduction performance. However, under the same conditions, the effect is the best when the copper-iron ratio is 5:5. From Figure 6 It can be seen that for the B, N co-doped carbon nanotube supported copper-iron bimetallic oxide material of the present invention, at a potential of -0.8 V RHE it can reach an ammonia production rate of 95.2 mgh -1 mg cat -1 and a Faraday efficiency of 91.3%; from Figure 7 It can be seen that the performance of the material is significantly improved when there is B doping; from Figure 8 It can be seen that when the pyrolysis temperature is 500 °C, the metal oxides on the surface of the carbon nanotubes agglomerate, their particles become significantly larger, and the density becomes smaller; from Figure 9 It can be seen from Figure 10 that among the materials with different copper-iron ratios, the performance is the best when the ratio of Cu to Fe is 5:5; from Figure 11 It can be seen from Figure 12 that when only 1 mmol of metal is added, its loading amount on the carbon nanotubes is significantly reduced.

[0045] Therefore, an appropriate copper-iron ratio, a reasonable metal loading amount, and a suitable pyrolysis temperature effectively increase the nitrate reduction performance of the material.

[0046] The present invention includes but is not limited to the above embodiments. Any equivalent replacement or partial improvement made under the spirit and principle of the present invention will be regarded as within the protection scope of the present invention.

Claims

1. A preparation method of a copper-iron bimetallic oxide catalyst supported on B, N co-doped carbon nanotubes, characterized in that It includes the following steps: (1) Uniformly mix an aromatic compound, boric acid, and urea in an organic solvent, and then remove the organic solvent; (2) Then place it in a tubular furnace and calcine it at 400 - 800 °C under an argon atmosphere to obtain B, N co-doped carbon nanotubes; (3) After washing, filtering, and drying the B, N co-doped carbon nanotubes obtained in step (2), soak them in a solution containing copper and iron metal ions, and then wash and dry; (4) Then place it in a tubular furnace and pyrolyze it at 300 - 480 °C for 1 - 4 hours in an inert gas atmosphere to obtain a B, N co-doped carbon nanotube-supported copper-iron bimetallic oxide catalyst.

2. The preparation method according to claim 1, characterized in that, The aromatic compound described in step (1) is one or more of perylene tetracarboxylic dianhydride, anthracene, quinone, and phenanthrene.

3. The preparation method according to claim 2, wherein When the aromatic compound is perylene tetracarboxylic dianhydride, the mass ratio of perylene tetracarboxylic dianhydride, boric acid, and urea added is 10:0.1 - 10:80 - 89.

8.

4. The preparation method according to claim 1, characterized in that, The organic solvent described in step (1) is ethanol.

5. The preparation method according to claim 1, wherein The solution containing copper and iron metal ions described in step (3) is a mixed solution of copper chloride and iron chloride.

6. The preparation method according to claim 5, characterized in that, The mass ratio of copper chloride to iron chloride is 1 - 10:1 - 10.

7. The preparation method according to claim 6, characterized in that, The addition amount of the B, N co-doped carbon nanotubes in step (3) is 100 - 300 mg, and the addition amount of the mixed solution of copper chloride and iron chloride is 1 - 4 mmol.

8. The B, N co-doped carbon nanotube-supported copper-iron bimetallic oxide catalyst prepared by the preparation method according to any one of claims 1 - 7.

9. Use of the copper-iron bimetallic oxide catalyst supported on B, N co-doped carbon nanotubes according to claim 8, characterized in that, It is used for nitrate reduction to produce ammonia and nitrate degradation.

Citation Information

Patent Citations

  • Ternary Mn-Cu-FeOx / CNTs denitration catalyst and preparation

    CN105289640A

  • Carbon nanotube composite material as well as preparation method and application thereof

    CN116272998A